Visualization of Aneurysmal Neck and Dome after Coiling with 3D Multifusion Imaging of Silent MRA and FSE-MR Cisternography - Satoh, T.; Hishikawa, T.; Hiramatsu, M.; Sugiu, K.; Date, I. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Our aim was to visualize the precise configuration of the aneurysmal neck and dome with/without remnants combined with a coiled dome after coiling treatment for cerebral aneurysms. We developed 3D multifusion imaging of silent MRA and FSE-MR cisternography.MATERIALS AND METHODS: We examined 12 patients with 3D multifusion imaging by composing 3D images reconstructed from TOF-MRA, silent MRA, and FSE-MR cisternography. The influence of magnetic susceptibility artifacts caused by metal materials affecting the configuration of the aneurysmal complex with coiling was assessed in a single 3D image.RESULTS: In all cases, TOF-MRA failed to depict the aneurysmal neck complex precisely due to metal artifacts, whereas silent MRA delineated the neck and parent arteries at the coiled regions without serious metal artifacts. FSE-MR cisternography depicted the shape of the coiled aneurysmal dome and parent artery complex together with the brain parenchyma. With the 3D multifusion images of silent MRA and FSE-MR cisternography, the morphologic status of the coiled neck and parent arteries was clearly visualized with the shape of the dome in a single 3D image.CONCLUSIONS: Silent MRA is a non-contrast-enhanced form of MRA. It depicts the coiled neck complex without serious metal artifacts. FSE-MR cisternography can delineate the shape of the coiled dome. In this small feasibility study, 3D multifusion imaging of silent MRA and FSE-MR cisternography allowed good visualization of key features of coiled aneurysms. This technique may be useful in the follow-up of coiled aneurysms.AComAanterior communicating arteryMRCMR cisternography